A novel 3D network nanostructure constructed by single-crystal nanosheets of B4C. Issue 18 (15th December 2017) - Xu, Juan; Liu, Xun; Wang, Shanqiang; Ma, Yongjun; Pei, Chonghua; Duan, Xiaohui
Abstract: Three-dimensional (3D) network nanostructure boron carbide was successfully synthesized via the carbothermic method. The carbon source and template was carbonized bacterial cellulose (CBC) with a 3D network nanostructure, and the boron source was B2 O3 and amorphous B powder. X-ray diffraction (XRD), Raman spectroscopy, field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM) and X-ray photoelectron spectra (XPS) were used to study the morphology and structure of the samples. XRD and Raman spectra confirm that they belong to the B4 C crystalline phase. The FESEM images show that the synthetic B4 C retains the 3D network nanostructure of the template CBC well and consists of B4 C nanosheets with an average thickness of less than 100 nm. The analytical results of high-resolution TEM (HRTEM) and Selected Area Electron Diffraction (SAED) indicate that the B4 C takes the shape of hexagonal single crystals with a rhombohedral structure. These B4 C single crystal nanosheets alternate, forming the 3D network nanostructure. The mechanism of formation can be accounted for by in situ reduction reactions along the carbon nanofibers of CBC.